Propofol pharmacokinetics in young healthy Indian subjects - Puri, Avinash (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: To analyze population pharmacokinetics of Propofol in Indian patients after single bolus dose of Propofol using WINNONLIN program. MATERIALS AND METHODS: Population pharmacokinetics of Propofol was investigated in Indian subjects in 26 elective surgical patients (14 males and 12 females) following single bolus dose of 2 mg/kg propofol. A total of 364 samples were estimated by High Performance Liquid Chromatography and pharmacokinetic parameters were derived using WINNONLIN (5.2). The effect of demographic characters of the study population on pharmacokinetic parameters was investigated. RESULTS: Three-compartment model was used to describe the pharmacokinetic data of Propofol in Indian subjects. Initial volume of distribution (V1) clearance (Cl) and steady state volume of distribution (Vd(ss)) was 13.5 ± 3.3 l, 1.08 ± 0.42 l/min, and 77.69 ± 48.0 l, respectively. Body weight best described the volume of central compartment (V1) as well as elimination clearance (P<0.01). CONCLUSION: Pharmacokinetics of Propofol in young healthy Indian subjects show lower volume of distribution and clearance as compared with most of the western data. Body weight best describes the V1, Vd(ss), and Clearance in this group.